CaF2 solubility in NaC1-KC1 salt flux for aluminium recycling - A. Sydykov; B. Friedrich; E. Milke; A. Arnold (The Southern African Institute of Mining and Metallurgy, 2004)
CaF2is often used as a fluoride addition to the chloride salt flux in the melting of aluminium scrap. The solubility of CaF2in the chloride salt system is limited. Dissolved CaF2is considered to improve the properties of salt fluxes. Experimental investigations indicated that the solubility ofCaF2in 70 wt % NaCl/30 wt % KCl, German salt flux used in aluminium scrap melting, might be lower than expected according to literature data. The pseudo binary section CaF2-(70 wt % NaCl-30 wt % KCl) was investigated by differential thermal analysis (DTA). The determined solubility of CaF2appeared to be considerably lower than presented in the literature. The pseudo binary section calculated using thermodynamic data partially confirmed the results. DTA allowed us alsoto determine the crystallization temperature interval of the two phase eutectic consisting of the solid solution NaCl-KCl and CaF2. Keywords: aluminium recycling, phase system, salt flux, CaF2, NaCl, KCl, solubility